Adaptive observer-based attack location and defense strategy in smart grid. (February 2022) - Wang, Wenting; Ma, Qiang; Lin, Lin; Guan, Ti; Tian, Dawei; Li, Shuqi; Li, Jian
This article mainly focuses on the attack location and defense of cyber-physical power systems under dynamic load altering attacks. Taking the smart grid as an example, first, the cyber-physical power system model under attack is established to provide conditions for attack detection. On this basis, an adaptive observer withH ∞ performance is designed to realize detection and location through residual signal and attack estimation, respectively. Furthermore, a power redistribution strategy based on optimal economic scheduling is presented to realize attack defense by means of the observer data. Finally, theoretical analysis proves the feasibility of the algorithm, and simulation cases prove the effectiveness of attack location and defense strategies.